Some Convexity Properties of Certain General Integral Operators - Vasile Marius Macarie; Daniel Breaz (Abstract and Applied Analysis)
The main object of the present paper is to discuss some extensions of certain integral operators and to obtain their order of convexity. Several other closely related results are also considered.